TRNSYS dynamic digital twin of hot and cold sensible thermal energy storages: An experimental calibration and validation approach - Rosato, Antonio; El Youssef, Mohammad; Daoud, Hussein; Al-Salaymeh, Ahmed; Ghorab, Mohamed Gaber (Journal of energy storage, 2025)
Sensible Thermal Energy Storages (STESs) are attracting significant interest thanks to the fact that they represent an effective solution to address the temporal mismatch between energy supply and energy demand. In this paper, a dynamic simulation model of typical STESs has been developed by using the software TRNSYS 18. The model has been calibrated and validated based on the data measured during a series of field experiments focused on both a hot as well as a cold vertical cylindrical 0.3 m3 STES equipped with a single internal heat exchanger (IHX). Furthermore, a simulation model has been developed to evaluate the impact of thermal stratification in tanks through the consideration of two distinct configurations, comprising 4 and 20 isothermal tank nodes. The experimental performances of the storages have been analyzed with reference to charging, discharging, simultaneous charging and discharging, natural heat up/cooldown tests, as well as typical daily operation to calibrate and validate the proposed model, providing key field data paving the way for future researches and developments of STESs. The simulation outputs have been compared with the experimental data by means of well-known statistical indicators. The comparison exhibited a good agreement in a wide range of operating conditions, with negligible differences between the 4-node and the 20-node configurations. In particular, the results highlighted reduced normalized root mean square deviations between experimental and simulated heat transfer fluid temperatures, with values ranging from 0.007 up to 0.141 in the case of the hot tank and varying between 0.007 and 0.333 in the case of the cold tank. In addition, acceptable percentage differences between predicted and field data in terms of daily energy during charging and discharging phases equal to −18.96 % and − 23.72 %, respectively, in the case of the hot tank and equal to 16.61 % and − 16.65 %, respectively, in the case of the cold tank have been recognized. The analysis underlined that the developed model accurately represents the dynamic and steady-state performance of both the hot and cold STESs, certifying its suitability in designing, analyzing as well as optimizing STES-based energy systems upon varying operating boundary scenarios. •Experimental performance analysis of hot and cold sensible thermal energy storages•Development of a TRNSYS dynamic digital twin of sensible thermal energy storages•Calibration and validation of TRNSYS dynamic digital twin based on measured data•Comparison between experimental and simulated performance data•Simulation model suitable in optimizing the design of storage-based energy systems